Empowering Communities Through Innovative Non-Formal Educatipn: A Case Study From The Community Learning Activity Centre Tenggang Raso, Indonesia - Nurul Hayati; Elih Sudiapermana; Asep Saepudin (STKIP Singkawang, 2025)
Non-formal education (NFE) is a vital catalyst for empowering individuals and communities, especially within the transformative landscape of Industry 4.0. This study critically examines the intersection of NFE innovation and empowerment, encompassing theoretical foundations, empirical studies, and case studies illuminating the transformationative potential inherent in innovative NFE practices. The case study at the community learning activity centre Tenggang Raso in Indonesia is a compelling case where an innovative learning model seamlessly integrates vocational skills into its curriculum. The findings from field observations and interviews highlight the innovative and creative aspects of the learning model, emphasising practical skills and entrepreneurship to enhance individual employability and contribute to broader community development and empowerment. In addition, the findings underscore the efficacy of integrating practical life skills and vocational training in enhancing participant engagement and fostering socio-economic development. This research underscores the need for continuous innovation, strategic collaborations with local industries, and a focus on gender equality to ensure that NFE remains a dynamic force for individual empowerment and community development in the future